Electrochromic poly(N-alkyl-3, 4-dihydrothieno[3, 4-b][1, 4]oxazine)s via electrosynthesis from green microemulsions. (10th July 2018) - Zhang, Wenwen; Zhang, Wenna; Xue, Zexu; Xue, Yu; Jian, Nannan; Qu, Kai; Gu, Hua; Chen, Shuai; Xu, Jingkun
Abstract: In the era of miniaturization researchers are looking for electrochromic materials that combine cost-effective production technology, environmental stability and high performance. It has already been demonstrated that conducting polymers are ideal candidates for electrochromic applications. Herein, Electrosynthesis of poly(N-methyl-3, 4-dihydrothieno[3, 4- b ][1, 4]oxazine) (PMDTO) and poly(N-ethyl-3, 4-dihydrothieno[3, 4- b ][1, 4]oxazine) (PEDTO) were performed in green microemulsions (H2 O, EtOH (ethanol) and Mix (H2 O/EtOH)) containing LiClO4 and poly(styrenesulfonic acid) (PSSH). The onset oxidation potentials ( E onset ) of monomers in these microemulsions were lower than those in common organic electrolytes, but the addition of PSSH brought increased E onset (ca. 0.15 V) versus direct electropolymerization in H2 O/LiClO4 electrolyte. SEM images show that PMDTO and PEDTO films obtained in H2 O/PSSH/LiClO4 present smooth, tight morphology. Spectroelectrochemistry results indicate that their electrochromic performance comparable with that in organic solvents, and significantly improved optical kinetic stability in H2 O electrolyte was observed, for which films under 1000s optical switching with little optical degradation. Based on these results, it is apparent that those polymers and systems have potential in electrochemical applications such as electrochromic devices and supercapacitors. Graphical abstract: Image 1 Highlights: Facile electrosynthesis of PMDTO and PEDTO in green microemulsions. A synergic effect forming H-bonding among N-alkyl group, PSSH and H2 O is proposed. Electrochromic performances were comparable with that in organic solvents. PMDTO and PEDTO films show greatly improved optical stability in H2 O.